Student Perspectives on Social Problems in Indonesia: A Documentation Study on Primakara University Student Articles - Alam, Helmy Syakh; Putri, Ni Wayan Nanik Suaryani Taro; Ayundia, Ni Kadek Yenni (ASANKA : Journal of Social Science and Education, 2025)
Social problems in Indonesia, such as corruption, drug abuse, and bullying, remain significant challenges impacting national development and social integrity. This study explores students' perspectives on these issues through a documentation study of 86 reflective articles written by Primakara University students. Using a qualitative descriptive approach with thematic analysis, the study identifies dominant themes and validates findings with national data and academic literature. The results reveal that students are highly aware of social issues and propose solution-based recommendations emphasizing education, empathy, and policy reform. These insights align with successful practices from Finland, Portugal, and Denmark. The study underscores the importance of student participation in social development and the need for progressive educational policies to support social change.